The negative predictive value of a negative repeat urinalysis in patients presenting with haematuria: A review of 1138 patients. (September 2017) - Starmer, Benjamin Zak; Singh, Amal; Bromage, Stephen
Objective: Haematuria may be transient for a number of benign conditions, particularly a urinary-tract infection (UTI). We set out to determine if a negative repeat urinalysis at the time of urological assessment for patients with haematuria could predict negative investigations and whether investigations could be tailored by this test. Methods: This was a retrospective analysis of records for all patients attending a haematuria clinic between 16 September 2013 and 12 September 2014. This included patients with visible and non-visible (microscopic) haematuria. Results: There were 1138 patients, 599 with visible haematuria (VH) and 460 with non-visible haematuria (NVH). Seventy-two patients were excluded. A total of 546 patients had a positive repeat urinalysis for blood; 438 patients had a negative repeat urinalysis when tested at the haematuria clinic, 298/599 for VH and 140/460 NVH. For those who had negative repeat urinalysis, urothelial cancer was found in 15/298 VH and 1/140 NVH. The one patient with negative repeat urinalysis and NVH was found to have a grade 2 (high grade) bladder tumour. The negative predictive value for a negative repeat urinalysis in transient haematuria was 0.95 for VH and 0.99 for NVH. Twenty-nine patients with VH and repeat negative urinalysis on assessment had a positive urine culture suggesting a UTI as a cause. None of these patients was found to have urothelial cancer ( p = 0.0413). Conclusion: Patients who experience transient VH and subsequent repeat negative urinalysis in the absence of infection have a 5% chance of urothelial cancer and should still be investigated. For those with transient NVH, the probability of finding a urothelial cancer is <1%, although we did find a high-grade bladder tumour in this group. If patients have a positive urine culture and a negative repeat urinalysis following treatment, they could be spared haematuria investigations.